Process Control of Activated Sludge Plants by Microscopic Investigation - H. Eikelboom, Dick (IWA Publishing, 2000)
Process stability and final effluent quality largely depend upon the composition of the biomass in an activated sludge plant. Operational problems such as bulking and scum formation occur when the wrong micro-organisms are dominating the sludge population. Microscopic sludge investigation is therefore essential for process control and stable plant operation. The manual outlines the theoretical framework, extensively illustrated with full-colour micrographs. Contents: - Microscopy - Microscopic sludge investigation - Characteristics of activated sludge flocs - Filamentous micro-organisms - Protozoa and metazoa - Conclusions of microscopic sludge investigation - The activated sludge process - Operational problems - Bulking sludge - Scum formation.